The Existence of Legal Politics in Realizing a Just State of Law - Ike Yuvayanti; Misranto; Moh. Muhibbin (JUSTITIA JURNAL HUKUM, 2025)
The rule of law aims to create justice, but in practice, legal politics is often influenced by the interests of economic and political elites. Injustice occurs due to regulations that favor certain groups over the welfare of the community at large. One example is regulatory changes in the mining sector that facilitate investment but ignore the rights of surrounding communities. This study aims to analyze the role of legal politics in realizing an equitable rule of law. This study explores how legal politics affects regulations, legal implementation, and its impact on society, especially in the context of mining policy. This research uses a normative method with a literature study approach. Secondary data is obtained from books, scientific journals, and relevant laws and regulations. The approaches used include statute approach, conceptual approach, and case approach to understand the influence of legal politics in public policy. legal politics in Indonesia still tends to favor the interests of the elite, resulting in inequality of justice. Inconsistent law implementation, weak rule of law, and political intervention in the judicial system hinder the realization of social justice. Regulations in the mining sector, for example, favor entrepreneurs over the welfare of local communities. Therefore, political legal reforms are needed that favor the interests of the people, strengthen the rule of law, and ensure the protection of human rights in order to create a just rule of law.